Building Self-Confidence in English Public Speaking through YouTube? Why Not? - Sri Wahyuningsih; Isna Silfiya Ni'mah (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
Self-confidence plays a pivotal role in public speaking, especially in English. Therefore, building students’ self-confidence is needed by using media including YouTube. The present study aims to elaborate on the role of YouTube in developing students’ self-confidence in English public speaking viewed from the student’s perspective. Further, some strategies used in developing students’ self-confidence are discussed. Using a qualitative method, the data of this study were gathered through a semi-structured interview with six students from the English Education Department of an Indonesian Islamic university. The findings reveal that most students have positive responses towards the use of YouTube as a medium to develop their self-confidence in English public speaking. In addition, they reported that YouTube plays a very crucial role in the development of their confidence in English public speaking. Importantly, they can comprehend the material more quickly, and develop their interest and motivation to learn. Finally, this study promotes the need for socialization from educational institutions in the development of English public speaking and the need to integrate the content of English public speaking with media and technology to enhance students’ learning success.